Effects of Standardized Ileal Digestible Lysine Content in Low Crude Protein Diets on Finishing Pig Performance and Economics from 230 to 280 lb - J. T. Gebhardt; M. A. Goncalves; M. D. Tokach; J. M. DeRouchey; R. D. Goodband; J. C. Woodworth; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2015)
The objective of this study was to estimate the nutritional requirement of standardized ileal digestible (SID) Lys on growth performance and economics of 230- to 280-lb finishing pigs housed in a commercial environment and fed diets not containing ractopamine HCl. A total of 1,101 gilts (PIC L327 × 1050, initially 233.4 lb BW) were used in a 28-d growth trial. Pens were blocked by BW and were randomly assigned to diets with 27 pigs per pen and 7 pens per treatment in a randomized complete block design. Diets were corn and soybean meal-based and fed in meal form, with dietary treatments consisting of: 0.52, 0.58, 0.64, 0.70, 0.76, or 0.82% SID lysine. Increasing SID Lys increased (linear, P<0.05) ADG and final BW, resulting in pigs fed 0.82% SID Lys having the greatest final BW. There was no difference in ADFI among pigs fed different SID Lys levels. Feed efficiency was improved (linear, P<0.05) with increasing SID Lys. In addition, there was an improvement (linear, P<0.05) in caloric efficiency on both a ME and NE basis with increasing SID Lys. Feed cost per pig increased (linear, P<0.05) as SID lysine level increased. However, there was no difference in feed cost/lb gain. Total revenue per pig increased (linear, P<0.05) while income over feed cost (IOFC) tended to increase (linear, P<0.07) as SID lysine level increased. Quadratic polynomial and broken-line linear models to maximize ADG resulted in similar fit and predicted the SID Lys level required to maximize ADG to be greater than 0.82 and at 0.685% SID Lys, QP vs. BLL, respectively. Using the QP model, 95% of the maximum growth was predicted to be at 0.675% SID Lys. The best F/G was achieved at greater than 0.82 and at 0.648% SID Lys for QP vs. BLL, respectively, with 95% of lowest F/G predicted at 0.638% SID Lys using the QP model. IOFC was maximized by the QP and BLL model at 0.754 and 0.640% SID Lys, respectively. In summary, the SID lysine requirement for optimal ADG, F/G, and IOFC of finishing pigs is at least 0.64% SID Lys.
Keywords: amino acid; growth; lysine requirement; finishing pig